PENGARUH LITERASI KEUANGAN, EFEK BANDWAGON DAN GAYA HIDUP HEDONIS TERHADAP PERILAKU KONSUMTIF MAHASISWA KLASTER EKONOMI UNIVERSITAS SILIWANGI PENGGUNA SHOPEE PAYLATER - Mochamad Ramdani; Rendra Gumilar; Iis Aisyah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research is motivated by the increasing interest in shopping on e-commerce with various paymnent options such as paylater, maing many people curious, including students majoring. However, on the other hand, this encourages students majoring to behave cosumtive. The aim of this research is to determine the extent of the influencve of financial literacy, bandwagon effect, hedonistic lifestyle on the consumtive behavior of Siliwangi University Economics Cluster students majoring, either simultaneously pr partially. This research uses a quantitative survey type research method with a design, namely an explanatory survey. The population in this study were students majoring from the Siliwangi University Economics Cluster. The sampling technique used was probability sampling, totaling 152 students majoring. The data collection technique uses a questionare and the data analysis technique uses the SPSS version 26 program. The research results show that: 1) there is a significant of financial literacy on consumer behavior with a calculated t value > t table (20,391 > 1,6892). 2) there is a significant influence of the bandwagon effect on consumer behavior with a calculated t value > t table (3,045 > 1,6892). 3) there is a significant influence of the hedonistic lifstyle on consumer behavior with a calculated t value > t table (3,293 > 1,6892). The conclusion of this research is that there is a significant influence between financial literacy, the bandwagon effect and a hedonistic lifestyle on the consumtive behavior of Siliwangi University Economics Cluster students majoring.